2014
DOI: 10.1007/s00059-014-4148-4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer antigen 125 levels and increased risk of new-onset atrial fibrillation

Abstract: CA-125 level is associated with the development of AF in patients with hospitalized systolic HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The increased CA-125 levels have been reported in different cardiac pathologies including CHF, coronary heart disease (CHD), AF and valve disease such as aortic stenosis and mitral stenosis. 5 - 7 , 11 , 12 Although there are few reports, the increased CA-125 levels is also documented in AMI. 7 - 9 …”
Section: Discussionmentioning
confidence: 99%
“…The increased CA-125 levels have been reported in different cardiac pathologies including CHF, coronary heart disease (CHD), AF and valve disease such as aortic stenosis and mitral stenosis. 5 - 7 , 11 , 12 Although there are few reports, the increased CA-125 levels is also documented in AMI. 7 - 9 …”
Section: Discussionmentioning
confidence: 99%
“…For ovarian cancer detection, the usual CA-125 cut-off level is >35 U/mL. 20 In contrast, Yucel et al 18 reported that the optimal cut-off level for CA-125 for predicting AF development was ≥68.49 U/mL in patients with systolic HF. Recently, Kaya et al 21 reported a retrospective cohort study where high CA-125 levels (≥91 U/mL) were predictors of the presence of permanent AF in patients with systolic HF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported the relationships between CA-125 and HF with reduced ejection fraction, HF with preserved ejection fraction 16 and ischaemic heart disease. 17 Yucel et al 18 reported that CA-125 levels are associated with the development of new-onset AF in patients hospitalised for systolic HF. However, no studies regarding the relationship between CA-125 and paroxysmal or persistent AF have been reported in healthy postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising, therefore, to find that AF, in the current study, is an independent predictor for prolonged hospitalization in patients with HF. 14,17,19,43,44 In addition to high CA-125 levels and the presence of AF, lower sodium levels and higher creatinine levels are associated with prolonged LOS. This result, consistent with previous studies, is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, in the last decade, a correlation between serum CA-125 levels and cardiopulmonary diseases such as left-and rightsided HF, coronary artery disease, atrial fibrillation (AF), and chronic obstructive pulmonary disease (COPD), has been revealed. [12][13][14][15][16][17][18][19] Although serum CA-125 levels are significantly increased in HF and this increase correlates with the severity of the disease, the relationship between CA-125 and length of stay (LOS) in patients with HF has not yet been evaluated. This study is the first that attempts to evaluate the relationship between the duration of hospitalization and CA-125 levels in patients with HF.…”
mentioning
confidence: 99%